Analysis of Waiting Time Factors and Patient Satisfaction Level in Diseases Poly in Hospital dr. Sayidiman Magetan - Novita Eka Sari; Indasah Indasah; Sentot Imam Suprapto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Good health care is a community need and is often a measure of development success. Recognizing that health services are a necessity for every citizen, the government endeavors from time to time to produce programs that can improve overall health services. Therefore, hospitals are required to always maintain trust by taking into account the needs of patients in an effort to fulfill the wishes and expectations of the services provided. Patients not only expect medical and nursing services but also expect comfort, good accommodation. Qualitative research is defined as a research procedure that produces descriptive data. Data collection using techniques indepth interview with semi-structured questions with a sample of 15 informants. From the results of the study note that services related to Waiting time get related to the speed of service procedures for patient acceptance, the accuracy of doctor arrival time and the speed of action, readiness of doctors and nurses to serve patients, distribution of medical record files from the medical record room to each poly and the ability of nurses is very influential to determine patient satisfaction by the treatment that patients get